THE INFLUENCE OF THE INFLUENCE OF AGE AND GENDER DEMOGRAPHICS AND INCOME LEVELS ON CONSUMERS' CHOICE TO USE CREDIT CARDS OR PAYLATER CREDIT AND OTHER NON-CARD LOANS CASE STUDY AT BANK BNI - Arrita, Rini (Riau International Conference on Economics, Business and Accounting, 2025)
This study investigates the impact of demographic factors on credit preferences among Bank BNI customers in Pekanbaru, Indonesia, amidst the evolving landscape of digital finance. Using a quantitative approach with a sample of 300 respondents, the research examines how age, gender, and income level influence choices between credit cards, paylater services, and non-card credit options. The study employs descriptive statistics, chi-square tests, and multinomial logistic regression to analyze the data. Results indicate a significant correlation between demographic characteristics and credit preferences. Credit cards remain the dominant choice (45.7%), particularly among older and higher-income customers, while paylater services (33.3%) are favored by younger generations. Gender differences reveal males have a higher preference for credit cards (50.6%) compared to females (39.9%). Income levels show a strong positive correlation with credit card preference, reaching 76.2% for the highest income bracket. Ease of use and competitive pricing emerge as the primary factors influencing credit choices. The multinomial logistic regression confirms that age, gender, and income significantly predict credit preferences. These findings have important implications for product development, marketing strategies, and risk management in the banking sector. The study contributes to the understanding of consumer behavior in the digital banking era and provides insights for financial institutions and regulators navigating the changing financial services landscape in Indonesia. It underscores the need for tailored, demographic-based approaches in credit product offerings to enhance market competitiveness and ensure financial inclusion.